(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Doronina T.A. Forming of a complete worldview of future teachers of foreign literature by means of historical and literary disciplines. The article is devoted to the problems of teaching the history of foreign literature in higher educational establishment of Ukraine, the possibility of forming of a complete picture of the world of future teachers of foreign literature by means of historical and literary disciplines is analyzed, using of the synchronic method as a mean of forming of a complete worldview of modern students - future teachers of foreign literature is actualized.